Jewish Life in Twenty-First-Century Turkey : The Other Side of Tolerance - Brink-Danan, Marcy (Book collections on Project MUSE., 2011)
Turkey is famed for a history of tolerance toward minorities, and there is a growing nostalgia for the "Ottoman mosaic." In this richly detailed study, Marcy Brink-Danan examines what it means for Jews to live as a tolerated minority in contemporary Istanbul. Often portrayed as the "good minority," Jews in Turkey celebrate their long history in the region, yet they are subject to discrimination and their institutions are regularly threatened and periodically attacked. Brink-Danan explores the contradictions and gaps in the popular ideology of Turkey as a land of tolerance, describing how Turki.